Screening and characterization of ß-glucosidase production by Saccharomyces cerevisiae - Sasithorn Sirilun (2018)
© 2016 Sasithorn Sirilun et al. Beta-Glucosidases (BGS) are the group of hydrolase enzymes, involved in the degradation processes and many biological processes. Due to demand, intensive screening of BGS is required to explore the natural microbial source of BGS. The current study deals with isolation and identification of BGS producing S. cerevisiae from Thai fruits & beverages and assessment of impact of pH, temperature, and salt concentration on BGS production. About 34 samples were collected. Yeast cells were isolated by plate method and characterized. About ten different strains were isolated and identified. The strain has been confirmed as S. cerevisiae through ribosomal sequencing. The optimization of BGS production was achieved by Box-Behnken design and Response Surface Methodology and confirmed that pH 4.0, temperature at 40 °C, and 0.5% of NaCl are optimum conditions. The kinetic analysis suggested that 24 h of incubation achieve the maximum yield. The reported S. cerevisiae strain could be the safer source for BGS. Further studies on enzyme recovery and purification will unbolt the way to attain high-quality microbial enzyme.